2012
DOI: 10.1093/carcin/bgs374
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-153 contributes to epithelial-mesenchymal transition and tumor metastasis in human epithelial cancer

Abstract: The epithelial-mesenchymal transition (EMT) is a crucial step in epithelial cancer invasion and metastasis. The aims of this study were to investigate and validate unidentified micro RNAs (miRNAs) that regulate EMT and to reveal their clinical relevance in epithelial cancer patients. By applying miRNA array screening in a natural epithelial-mesenchymal phenotype cell line pair and in a transforming growth factor β-induced EMT cell model, we found miR-153 was markedly downregulated in the cells that underwent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
79
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 46 publications
3
79
0
Order By: Relevance
“…miR-153 is down-regulated in cells that have undergone EMT by TGF␤ and inhibits tumor metastasis and EMT by targeting SNAI1 and ZEB2 (42). It will be interesting to examine the role of miR-153 in angiogenesis, invasion, and the response to microtubule-targeting drugs in relation to CAGE.…”
Section: Discussionmentioning
confidence: 99%
“…miR-153 is down-regulated in cells that have undergone EMT by TGF␤ and inhibits tumor metastasis and EMT by targeting SNAI1 and ZEB2 (42). It will be interesting to examine the role of miR-153 in angiogenesis, invasion, and the response to microtubule-targeting drugs in relation to CAGE.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al (2013) discovered that transient transfection of miR-153 in glioblastoma stem cells induces apoptosis. Furthermore, low expression level of miR-153 was found to be significantly related to metastasis and poor prognosis in oral cancer patients by targeting SNAI1 and ZEB2 (Xu et al, 2013). Additionally, abnormal downregulation of miR-153 can also be detected in human ovarian tumors and was correlated significantly with advanced clinical stage (Kim et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Downregulation of miR-206 was previously found to contribute to laryngeal cancer proliferation and invasion via regulation of VEGF expression (34), while VEGF was reported to be a predictor for HNSCC (35), implying that miR-206 may be an inhibitor for HNSCC. A previous study found that miR-1 inhibited cell proliferation of HNSCC by targeting TAGLN2 (36), and downregulation of miR-153 promoted tumor metastasis in human epithelial cancer by targeting ZEB2 (37). On the other hand, nucleotide biosynthesis is involved with tumor cell growth during cell proliferation (38).…”
Section: Discussionmentioning
confidence: 99%